GUNUNG API PURBA DI DAERAH BAKAUHENI - PULAU SANGIANG,SELAT SUNDA, KABUPATEN LAMPUNG SELATAN - S. Bronto; P. Asmoro; G. Hartono; S Sulistiyono (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Along the Merak - Bakauheni route, Sunda Strait, there are some island composing by Tertiary volcanic rocks. Relating to the plan of construction of Sunda Strait Bridge, several Tertiary and Quaternary volcanic islands at Merak – Bakauheni ferry route are examined as paleovolcanoes in order to evaluate their potential hazards. Methods that used in this study are remote sensing analyses of satellite image and topographic maps, and field geologic investigation. As results, three paleovolcanoes are recognized, namely Harimaubalak, Kandangbalak and Sangiang. To understand the history of their volcanic activities radiometric analyses are required. Those three paleovolcanoes are located in a line having NW – SE direction, considered as a weak zone because the pattern similarity with the active Sumatran fault system. To anticipate the possibilities of opening new vents or reactivated eruptions from the weak zone it is suggested to make further studies on seismicity, tectonic analyses, and the present of sub surface hot sources.Key words : bakauheni, harimaubalak, paleovolcano, sangiang, sunda strait, lampung